Membangun Animasi 2D Mitigasi Bencana Banjir Daerah Pinggiran Sungai Deli Menggunakan Metode 2D Hybird Animation - Septiawan, Ade Peruzi; Khairani, Sumi (Explorer, 2025)
Flooding is a natural disaster that frequently occurs in Medan City, particularly in residential areas located along the banks of the Deli River. To minimize the negative impacts of this disaster, educational media is needed to enhance public understanding of flood mitigation efforts. This study aims to develop an educational animation using the 2D Hybrid Animation method as a means of delivering information on flood disaster mitigation, specifically in Sei Mati Subdistrict, Medan Maimun District. This method combines traditional hand-drawn techniques with digital processing using Adobe Animate software, resulting in engaging and informative 2D animations. Based on trial results involving 25 respondents regarding flood disaster mitigation, the average pre-test score was 42, while the post-test score reached 94. This indicates an improvement of 41.6%. These results show that the animation media is effective in increasing respondents’ understanding of flood mitigation.